A purple place for dying - MacDonald, John D. (John Dann), 1916-1986 (MacDonald, John D. (John Dann), 1916-1986. Travis McGee series., 2013)
Travis McGee is summoned to Arizona by a rich, beautiful arrogant woman. And then she's dead - shot in the back at long range, lying crumpled on the ground at his feet. With the would-be client eliminated, and on a dime's worth of fee in his pocket, any ordinary detective would walk away fast. But Travis McGee is no ordinary detective.